2023
DOI: 10.1111/nph.18744
|View full text |Cite
|
Sign up to set email alerts
|

Hidden genetic variation in plasticity provides the potential for rapid adaptation to novel environments

Abstract: Rapid environmental change is forcing populations into environments where plasticity will no longer maintain fitness. When populations are exposed to novel environments, evolutionary theory predicts that genetic variation in fitness will increase and should be associated with genetic differences in plasticity. If true, then genetic variation in plasticity can increase adaptive potential in novel environments, and population persistence via evolutionary rescue is more likely.To test whether genetic variation in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…Having detected significant genotype-by-environment interactions for relative fecundity, we next determined the origin of this variation. GxE can be due to increased variation in relative fecundity on specific diets across genotypes (Walter et al, 2022; Sheth et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Having detected significant genotype-by-environment interactions for relative fecundity, we next determined the origin of this variation. GxE can be due to increased variation in relative fecundity on specific diets across genotypes (Walter et al, 2022; Sheth et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…We then went on to reveal the cause of this within-population G×E. Significant G×E can arise as the result of differences in the expression of genetic variation across environments and/or cross-environment genetic correlations that are less than one (Falconer 1952; Via & Lande 1985; Walter et al, 2022; Sheth et al, 2018). While some studies have found that exposure to environmental stress may increase the expression of genetic variance for life-history traits, including fecundity (Service & Rose, 1985; Van Noordwijk et al, 1988; Etges, 1993; Holloway et al, 1990; Larsson et al, 1997; Jenkins et al, 1997; Sgrò & Hoffmann, 1998), other studies suggest that this might depend on the trait and the environmental condition studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dramatic reduction in mean fitness beyond the range suggests that the novel conditions posed a challenge for most genotypes. However, a few genotypes with low fitness at the home site appeared ‘pre‐adapted’ to the new environment and enjoyed the highest fitness (nonsignificant correlation = −0.1; Walter et al ., 2023). Fitness trade‐offs between within‐ and beyond‐range environments could limit species' ranges if selection in native habitats quickly eliminated alleles that would be beneficial beyond the range, but this has rarely been tested in the field (Angert et al ., 2008).…”
Section: Fitness Trade‐offs and Bottlenecks Can Inhibit Beyond‐range ...mentioning
confidence: 99%
“…A novel approach examining the impact of variation in plasticity on the adaptive capacity of a population is used by Walter et al . (2023; pp. 374–387) in a new article published in this issue of New Phytologist .…”
mentioning
confidence: 99%